The Use of Online Travel Agent (OTA) By Non-Star Hotels in Sanur Bali - Sanjiwani, I Gusti Agung Mirah; Wiranatha, Agung Suryawan; Suryawardani, I Gusti Ayu Oka (E-Journal of Tourism; Volume 6 Number 2 (September 2019)DO - 10.24922/eot.v6i2.56514, 2019)
Non-star hotels as a tourism business are nowadays using online travel agents (OTA) to market their rooms. The research on using OTA is interesting to be conducted, considering that research involving hotel management in accepting technology using the Technology Acceptance Model (TAM) is has not widely found. This study aims to analyze the influence of non-star hotel management's acceptance in using OTA by TAM, namely Perceived Usefulness, Perceived Ease of Use, Attitude Toward Using, and Behavioral Intention to Use. The study involved 59 non-star hotel managements in Sanur as the respondents. The questionnaire included 17 indicators on TAM and interviews were conducted to support the statistical analysis. Structural Equation Modeling (SEM) analysis was carried out by using the SmartPLS 3 program. The results shows that: 1) Perceived Usefulness is significantly influenced on Attitude Toward Using, 2) Perceived Ease of Use is significantly influenced on Attitude Toward Using, 3) Perceived Usefulness is significantly influenced on Perceived Usefulness, 4) Attitude Toward Using is significantly influenced on Behavioral Intention to Use, and 5) Perceived Usefulness is not significantly influenced on Behavioral Intention to Use in hotel management of non-star hotels in Sanur Bali in using OTA. Overall, the non-star hotel management accepts OTA well to be used in their hotels. Keywords: Technology Acceptance Model, Online Travel Agent, Non-star Hotels Management, Bali.